Opal Entrepreneurship: Indigenous Integration of Sustainable Luxury in Coober Pedy - Condello, Annette (Springer, 2018)
In a world of diminishing resources, the opal has become a sign of mineral exclusivity for the consumer luxury market and its value as a luxury object comes from gemstone cognoscenti. According to one Australian Aboriginal legend, rainbow-hued opals are believed by some to stir emotions of loyalty and connection to the earth. Regarding the integral indigenous connection of Australia’s national gemstone, rarely has one has looked at the spaces where opal veins were once quarried in remote regions in terms of sustainable luxury. More importantly, the revival of South Australia’s opal mining industry in Coober Pedy by female Aboriginal entrepreneur Tottie Bryant in 1946; its development into a multi-million dollar industry into a modern hub in the 1970s; and the spread of the town’s construction of subterranean spaces a decade later, enticed immigrants to mine for opals. And when seeking an inexpensive and cool environment, the place enticed immigrants to live underground, providing an unusual form of sustainable luxury in Australia. In 1968, for instance, former Coober Pedy opal entrepreneur John Andrea planned for a unique international underground hotel, the luxurious Desert Cave, but it was not until 1981 when Umberto Coro realised the subterranean spaces’ potentiality and created Andrea’s dream. Another opal entrepreneur Dennis Ingram designed a golf course with ‘scrapes,’ which emerged above ground made with opal quarry dust and waste oil. In popular culture too, the town had attracted filmmakers, such as George Miller, to produce his post-apocalyptic epic Mad Max, and Wim Wenders, to document his wandering scenes not because of opal scarcity but due to the harsh desert-landscape littered with spoil heaps. Turning to adaptive reuse and indigenous culture in Coober Pedy, this chapter addresses the existing underground passages as the recyclable-integration of a former mining site. In tracking the way in which the community and its rural groundwork served as a site for an innovation in sustainable luxury, the remote underground passages has revealed an unusual Australian lifestyle. Concentrating on the underground spaces, the chapter tracks the manner in which the abandoned sites serve as poignant opal connections within Coober Pedy’s integration of remnant spaces and their adaptive reuse into museums. Opal museums of the future will become magnetic as tourist destinations and their conversion of remnant spaces also into educational facilities foresees the uniqueness of sustainable luxury through its existing empty quarries.